Protective Effect of Maternal Influenza Vaccination on Influenza in Their Infants: A Prospective Cohort Study. (5th December 2017) - Ohfuji, Satoko; Deguchi, Masaaki; Tachibana, Daisuke; Koyama, Masayasu; Takagi, Tetsu; Yoshioka, Takayuki; Urae, Akinori; Ito, Kazuya; Kase, Tetsuo; Maeda, Akiko; Kondo, Kyoko; Fukushima, Wakaba; et al.
Abstract : This prospective cohort study showed that the effectiveness of prenatal and postpartum influenza vaccination of mothers in preventing influenza among their infants was 61% and 53%, respectively. Maternal influenza vaccination during the prenatal or postpartum periods had beneficial effects in protecting infants from influenza. Abstract: Background: Infants <6 months of age are too young to receive influenza vaccine, despite being at high risk for severe influenza-related complications. Methods: To examine the effectiveness of maternal influenza vaccination in preventing influenza in their infants, we conducted a prospective cohort study of 3441 infants born at participating hospitals before the 2013–2014 influenza season. At the time of recruitment, their mothers completed a questionnaire about influenza vaccination status for the 2013–2014 season. A follow-up survey was conducted after the end of the 2013–2014 season to collect information regarding influenza diagnosis and hospitalization among infants. Results: During the 2013–2014 influenza season, 71 infants (2%) had influenza diagnosed, and 13 infants (0.4%) were hospitalized with influenza. Maternal influenza vaccination (especially prenatal vaccination) decreased the odds of influenza among infants. The effectiveness of prenatal vaccination was 61% (95% confidence interval, 16%–81%), whereas that of postpartum vaccination was 53% (−28%–83%). Although maternal influenza vaccination was also associated with a decreased odds of influenza-related hospitalization among infants, vaccine effectiveness (73%) did not reach statistical significance, owing to the limited number of infants hospitalized because of influenza. Conclusions: The present findings indicated that pregnant women and postpartum women should receive influenza vaccination to protect their infants.